Partial removal and detoxification of Malachite Green and Crystal Violet from laboratory artificially contaminated water by Pleurotus ostreatus - Claudia Marcela Rivera-Hoyos; Natalia González-Ogliastri; Refugio Rodríguez-Vázquez; Raúl Alberto Poutou-Piñales; Carlos Enrique Daza; Aura Marina Pedroza Rodriguez (Universitas Scientiarum)
The triphenylmethane dyes Malachite Green (MG) and Crystal Violet (CV) are cationic dyes and mix with domestic wastewater when dumped; increasing, among others, the chemical and biological demand of oxygen and can cause acute toxicity at different trophic levels. Promoting the removal (decolorization) of MG and CV, and laccase activity (54.8 ± 8.9 and 30.6 ± 2.9 UL-1 respectively) by using P. ostreatus viable biomass needed parameters such as pH (4.5 and 6.0), temperature (25 to 30 °C), stirring speed (120 rpm), percentage of inoculum (2% v/v), and dye concentration (20 and 10 mg L-1). In adsorption studies, it was showed that an acidic pH favors the adsorption of both dyes and the model of pseudo-second order describes best the phenomenon of adsorption. Finally, the germination index (GI), using Lactuca sativa seeds for the initial dyes solutions, was <50%; demonstrating its high phytotoxic effect. When dye solutions were treated with viable biomass, the GI increased, leaving open the possibility to performing future research to determine if the aqueous solutions, post-treated with P. ostreatus, could be used in treatments that generate less toxic water which could be used in processes that do not require potable water.